2011
DOI: 10.1002/ange.201007557
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy‐Level Tuning of Silver Nanoparticles for Facilitated Olefin Transport

Abstract: Tetracyanchinodimethan (TCNQ) auf Silbernanopartikeln (AgNPs) induziert hohe positive Oberflächenladungen, die einen Grenzflächendipol erzeugen, über den sich die Energieniveaus der AgNPs einstellen lassen (siehe Bild). Poly(vinylpyrrolidon)‐Membranen, die dispergierte AgNPs mit TCNQ enthalten, zeigen eine hohe Selektivität bei der Trennung gasförmiger Olefin‐Paraffin‐Gemische.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…When ionic liquids such as 1-butyl-3-methyl imidazolium tetrafluoroborate and 1-butyl-3-methyl imidazolium nitrate were incorporated into poly(2-ethyl-2-oxazoline) (POZ)/AgNO 3 complex membranes, AgNO 3 could play a role as olefin carrier due to the weakened interactions between Ag þ and counteranions with longterm stability [24]. Furthermore, the Ag NPs were suggested as new olefin carrier for long-term stability [25][26][27][28]. Our group reported that when Ag NPs were positively polarized by specific electron acceptors such as p-benzoquinone, 7,7,8,8-tetracyanoquinodimethane, and ionic liquids, the surface of nanoparticles could be reversibly interacted with olefin molecules, resulting in the facilitated transport [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When ionic liquids such as 1-butyl-3-methyl imidazolium tetrafluoroborate and 1-butyl-3-methyl imidazolium nitrate were incorporated into poly(2-ethyl-2-oxazoline) (POZ)/AgNO 3 complex membranes, AgNO 3 could play a role as olefin carrier due to the weakened interactions between Ag þ and counteranions with longterm stability [24]. Furthermore, the Ag NPs were suggested as new olefin carrier for long-term stability [25][26][27][28]. Our group reported that when Ag NPs were positively polarized by specific electron acceptors such as p-benzoquinone, 7,7,8,8-tetracyanoquinodimethane, and ionic liquids, the surface of nanoparticles could be reversibly interacted with olefin molecules, resulting in the facilitated transport [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Ag NPs were suggested as new olefin carrier for long-term stability [25][26][27][28]. Our group reported that when Ag NPs were positively polarized by specific electron acceptors such as p-benzoquinone, 7,7,8,8-tetracyanoquinodimethane, and ionic liquids, the surface of nanoparticles could be reversibly interacted with olefin molecules, resulting in the facilitated transport [25][26][27]. To enhance the permeance for nanocomposite membrane, poly(ethylene oxide) (PEO)/AgNPs/p-benzoquinone composite membrane was prepared, which showed the increased gas permeance, i. e. 15 GPU [28].…”
Section: Introductionmentioning
confidence: 99%
“…When the AgBF 4 silver salt is dissolved in poly(vinylpyrrolidone) (PVP) or poly(ethylene oxide) (PEO) a solid polymer electrolyte forms and free silver ions are generated. The silver ions were observed to reversibly form complexes with olefins, which indicate that they could be used to transport olefins across the membrane . However, facilitated transport by silver ions has a significant disadvantage that can trigger a lower output: the reduction of silver ions with time .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the disadvantage of these ions being reduced with time, a new facilitated transport method has recently come into the spotlight based on the discovery that a positive charge on the silver nanoparticles (AgNPs) can cause reversible reactions with olefins, resulting in the AgNPs acting as carriers for the olefins . The carriers form a reversible complex with particular components and enhance the transport rate of that component.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, there have been significant advances in photovoltaics, electrochemistry, separation science and catalysis due to bimetallic composites [1][2][3][4][5][6]. By changing the composition of inorganic bimetallic composites, the properties of these materials can be tuned [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%